Interactive Metadiscourse on Joe Biden’s Presidential Speeches - Akbar, Fariz Fadillah; Ekawati, Rosyida (LingPoet: Journal of Linguistics and Literary Research, 2024)
This research examines the use of interactive metadiscourse markers in three presidential speeches delivered by President Joe Biden, with a focus on transition markers, frame markers, endophoric markers, evidence, and code glosses. It used descriptive qualitative method. The analysis is based on the metadiscourse model by Hyland (2005). Findings showed that transition markers, especially those indicating addition, were the most frequently used, followed by frame markers, endophoric markers, code glosses, and proofs. This study shows how these markers contribute to the coherence and persuasiveness of speech by guiding audience interpretation, organizing discourse, and clarifying intended meaning. In particular, the study identified examples where one marker, for example, had multiple functions across different categories. This study contributes to the understanding of metadiscourse in political speech and highlights the role of such markers in enhancing the effectiveness of presidential communications.